ANALISIS PERBANDINGAN HUKUM PIDANA INDONESIA DAN ISLAM : SANKSI PELAKU SERTA KEADILAN BAGI KORBAN PENGANIAYAAN - NIM. A1011211271, UMMI ROHIMAH (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract The phenomenon of abuse as a form of physical violence remains prevalent in society and is a significant concern in criminal law. In Indonesia